Cultivar differences in the hormonal crosstalk regulating apple fruit development and ripening: Relationship with flavour components and postharvest susceptibility to Penicillium expansum - Fernández-Cancelo, Pablo; Echeverria, Gemma; Teixidó, Neus; Alamar, M. Carmen; Giné-Bordonaba, Jordi (Elsevier, 2023)
The hormonal interplay during the on-tree development and ripening of three apple cultivars with known differences in their postharvest ripening patterns was studied, at the biochemical and targeted gene expression level, along with characterizing the changes in main sugars, acids, phenylpropanoids and volatile organic compounds (VOCs). Our findings suggest that in ‘Royal Gala’ and ‘Opal®’ apples, a peak in indole 3-acetic acid (IAA) seems necessary to activate ethylene metabolism, being its intensity proportional to the ethylene production. The interplay between IAA and ethylene appears to be mediated by MdARF5, responsible for activating the expression of MdACS3 and triggering ethylene metabolism. On the other hand, the lack of ethylene production observed in ‘Granny Smith’ apples was likely related to the absence of an IAA peak and possibly caused by the over activation of IAA conjugation mechanisms leading to a greater accumulation of IAA inactive conjugates such as indole-3-acetyl-aspartate (IAAsp). Abscisic acid (ABA) accumulation was only observed in cultivars with the ability to accumulate sucrose and produce ethylene, suggesting a possible crosstalk among those hormones and sucrose in orchestrating apple on-tree ripening. While differences in hormone levels among cultivars led to noticeable differences in some specific VOCs, no evident associations were found between hormone changes and the accumulation or degradation of monosaccharides, organic acids or phenolic compounds during fruit development and ripening. Likewise, no clear relationship was found between the fruit susceptibility to blue mould and hormonal levels yet certain specific biochemical compounds (i.e., procyanidins and sucrose) could be acting as a source of resistance or susceptibility, respectively, to blue mould development. Overall, understanding the cultivar specific hormonal regulation of apple on-tree ripening provides valuable insights to optimize fruit quality at the time of harvest as well as to develop strategies for improved postharvest management.
Keywords: Abscisic acid (ABA); Blue mould; Ethylene; Indole 3-acetic acid (IAA); MdARF5; Procyanidin; Sucrose